Effect of High Dose Inhaled Acetic Acid on Airway Responsiveness in Fischer Rats - AP Ariel; HG Furlott; KR Chapman; AS Slutsky; P Webster; N Zamel; SM Tarlo (Canadian Respiratory Journal)
BACKGROUND: Sudden, severe airway injury has been associated with an acute, and at times persisting, airway hyper-responsiveness with clinical features of asthma, termed reactive airways dysfunction syndrome (RADS). An attempt was made to develop a rat model of RADS by exposing inbred Fischer rats to inhaled 8 N acetic acid for 2 mins (13 N inhalation was lethal).